Morphology of Van der Waals surfaces and magnetic hysteresis in cobalt intercalated InTe - Boledzyuk, V.B.; Kovalyuk, Z.D.; Kudrynskyi, Z.R.; Shevchenko, A.D. (Functional Materials, 2015)
The influence of Co²⁺ intercalation on the properties of InTe monocrystals was investigated. The intercalation of cobalt in InTe are not leading to change of the crystal lattice parameters, leaving the same structural type of the samples. It is established that in investigated intercalates on the Van der Waals surfaces of InTe layers there is formation clusters impurity, which consist from cobalt nanoparticles of the pyramidal form. Cobalt intercalated InTe possesses ferromagnetic properties: the dependence of its magnetic moment from magnetic field has the form of hysteresis loop that is characteristic for ferromagnets.